Erster Beitrag zur Kenntnis der Parasiten von Exoteleia dodecella L. (Hymenoptera: Chalcidoidea; Proctotrupoidea; Bethyloidea). - Lemarie, Jaroslav (Contributions to Entomology = Beiträge zur Entomologie, 1959)
Nearly twenty parasitic, or hyperparasitic, Hymenoptera were reared from Exoteleia dodecella L. Only three of these, viz. Copidosoma geniculatum Dalm., Cirrospilus pulcherrimus Mercet, and Tetrastichus turionum Htg. were reared in great numbers; the emergence of the remaining species was much less frequent or singular.